2010
DOI: 10.1007/s12571-010-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Getting the focus right: production constraints for six major food crops in Asian and African farming systems

Abstract: To determine the most important production constraints and associated yield losses for six major food crops in 13 farming systems with high poverty in SubSaharan Africa, South Asia and East Asia, surveys were conducted with 672 experts representing a diversity of backgrounds and experience. Respondents reported large gaps between highest achieved crop yield on smallholder farms and average yield on farm. Yield gaps were smallest for rice (about 60% of current average smallholder farm grain yields), mid size fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 24 publications
(30 reference statements)
3
139
0
Order By: Relevance
“…Areas of sub-Saharan Africa suffer severe food insecurity, relatively low-yielding croplands, and the potential for large relative yield gains (131). Closing yield gaps requires addressing a host of interacting agronomic and socioeconomic constraints (88,105,145). The joint evolution of agricultural development and global environmental change will together determine future levels of crop productivity.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Areas of sub-Saharan Africa suffer severe food insecurity, relatively low-yielding croplands, and the potential for large relative yield gains (131). Closing yield gaps requires addressing a host of interacting agronomic and socioeconomic constraints (88,105,145). The joint evolution of agricultural development and global environmental change will together determine future levels of crop productivity.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Waddington et al [43] studied yield constraints for six major food crops in Africa and Asia based on surveys made of 13 farming systems. The authors identified four major categories of constraints, namely abiotic, biotic, management, and socio-economic.…”
Section: Constraints To Productivity Of Crops Cultivated In Africamentioning
confidence: 99%
“…Waddington et al 2010;Kelley et al 1995). This methodology does not account for spatial and temporal variability of particular constraints or potential biases of those surveyed, or the survey takers, so it seems prudent to use such information to support field experimentation rather than to replace it.…”
Section: Diagnosis Of Constraintsmentioning
confidence: 99%